Fast unconditional initialization for superconducting qubit and resonator using quantum-circuit refrigerator - Yoshioka, T.; Tsai, J. S. (Applied physics letters, 2021)
In a quantum computation scheme, such as recycling a qubit, the initialization of the qubit is always required. At present, the initialization of the qubit is one of the bottlenecks in such computation, and high fidelity and fast initialization still remain important research subjects. In this study, by coupling a SINIS (superconductor–insulator–normal metal–insulator–superconductor) junction to a coupled system consisting of a qubit and a resonator, a photon is removed from the resonator by single-photon-assisted tunneling, and the effective relaxation rate of the resonator is increased. In addition, by applying an | e , 0 ⟩ − | f , 0 ⟩ drive pulse and an | f , 0 ⟩ − | g , 1 ⟩ drive pulse to the qubit, the energy of the qubit is rapidly transferred to the resonator to realize high-speed initialization. The present simulation shows that the qubit can be initialized with 99% fidelity in 80 ns and 99.9% in 137 ns when the electron temperature of the normal metal of the SINIS junction is 10 mK. The simulation also shows that the relaxation time of the qubit is about 13% longer when the resonator is interposed between the SINIS junction and the qubit than when the SINIS junction is directly coupled to the qubit.